Can testosterone replacement decrease the memory problem of old age? - Lim, David; Flicker, L.; Dharamarajan, A.; Martins, R. (Churchill Livingston, 2003)
The world is rapidly ageing. It is against this backdrop that there are increasing incidences of dementia reported worldwide, with Alzheimer's disease (AD) being the most common form of dementia in the elderly. It is estimated that AD affects almost 4 million people in the US, and costs the US economy more than 65 million dollars annually. There is currently no cure for AD but various therapeutic agents have been employed in attempting to slow down the progression of the illness, one of which is oestrogen. Over the last decades, scientists have focused mainly on the roles of oestrogen in the prevention and treatment of AD. Newer evidences suggested that testosterone might also be involved in the pathogenesis of AD. Although the exact mechanisms on how androgen might affect AD are still largely unknown, it is known that testosterone can act directly via androgen receptor-dependent mechanisms or indirectly by converting to oestrogen to exert this effect. Clinical trials need to be conducted to ascertain the putative role of androgen replacement in Alzheimer's disease.